Three stories from the margins of Lithuanian heritage protection - Lukšionytė, Nijolė (Journal of Architecture and Urbanism, 2012)
The article discusses three objects of Kaunas architectural heritage, which represent different cases of heritage treatment in the years of independence. In Soviet times, a building of the Communist Party Committee blocked the gothic church of St Gertrude to an enclosed yard. This building was demolished by the civic initiative organised by the Sąjūdis movement in 1989. The church was restored using the state funds in 1991–1994.A small wooden suburban manor was built in Baritonai Street in the middle of the 19th century. It had belonged to the Petravičiai family for one hundred years. The house has been deserted since 1994. The local authority of Kaunas has been working on privatisation documents for so long that the house has entirely crumbled.A detached house of the famous architect Vytautas Landsbergis-Žemkalnis represents the interwar modernism. After restoration of independence, it was returned to his family. The family sold the house. Although it was included to the Register of Cultural Property and declared protected by the state, the new owners have transformed the exterior of the house completely in 2004–2005.The two last-mentioned examples symptomatically reveal a crisis of values in Lithuanian heritage protection. A punctilious legalism enables institutions responsible for heritage protection to hide under the veil of law-making rather than bother with alternative possibilities of preservation.Article in Lithuanian.Iš Lietuviškos paveldosaugos paraščių: trys istorijosSantrauka. Straipsnyje aptariami trys Kauno architektūros paveldo objektai, reprezentuojantys skirtingus elgesio su paveldu atvejus nepriklausomybės metais. Gotikinę Šv. Gertrūdos bažnyčią į uždarą kiemą užblokavęs komunistų partijos komiteto pastatas buvo nugriautas Atgimimo sąjūdžio organizuotos visuomenės iniciatyva 1989 m., o pati bažnyčia 1991–1994 m. restauruota valstybės lėšomis. Medinis XIX a. vidurio priemiesčio dvarelis Baritonų g. 6, šimtą metų priklausęs Petravičių šeimai, nuo 1994 m. stovi tuščias, miesto savivaldybė tol rengė dokumentus privatizacijai, kol namas visai sugriuvo. Žymaus architekto Vytauto Landsbergio-Žemkalnio kotedžas, reprezentuojantis tarpukario modernizmą, atkūrus nepriklausomybę buvo grąžintas šeimai. Jos nariai namą pardavė, naujieji savininkai 2004–2005 m. visiškai pertvarkė išorę, nors objektas jau buvo įtrauktas į Kultūros vertybių registrą ir paskelbtas valstybės saugomu. Šie du pavyzdžiai simptomiškai atskleidžia vertybių krizę Lietuvos paveldo apsaugos srityje. Utilitarus legalizmas leidžia paveldosaugos institucijoms prisidengti įstatymo formule ir nesivarginti ieškant alternatyvių išsaugojimo galimybių.Reikšminiai žodžiai: Kauno architektūra, Šv. Gertrūdos bažnyčia, Baritonų g. 6, Donelaičio g. 38, paveldo apsauga, vertybių krizė.